Impact of covid-19 pandemic in hospitalizations of women with endometriosis: Ecological study (Revista Contexto & Saúde, 2025)
Objective: to analyze the impacts of the covid-19 pandemic on hospitalizations of women with endometriosis in Brazil. Method: this is an ecological epidemiological study, retrospective, based on documentary and quantitative approach, which followed the recommendations of STROBE. Data on hospital admissions for endometriosis were collected through the hospital information system based on DATASUS, between 2018 and 2021. Results: in 2018 and 2019 there were 12,406 and 11,989 hospitalizations of women with endometriosis. In the years 2020 and 2021 there were 7,202 and 7,759 hospitalizations, showing a decrease of about 40% compared to previous years. The prevailing age group was between 40 and 49 years (42%) and as for race/color, in 2018 and 2019 it was the white race and in 2020 and 2021 the brown race. As for the region of residence, more occurred in the southeastern region (43%), as well as the states of São Paulo (18%) and Minas Gerais (16%). Regarding the character of the service, most was elective. Conclusion: it was evidenced that the pandemic impacted on hospital admissions of women with endometriosis, who presented a white color/race profile, aged between 40 and 49 years, living in the southeastern region of the country, mainly in the states of São Paulo and Minas Gerais.
Keywords: Endometriosis; Coronavirus; Pandemic; Hospital; Nursing